The HCF of two expressions p and q is 1. What is the reciprocal of their LCM?

  1. p + q
  2. p – q
  3. pq
  4. (pq)-1


The product of two polynomials is equal to the product of their HCF and LCM.

HCF × LCM = pq

Given, HCF = 1

So, LCM = pq

1/LCM = (pq)-1

The correct option is D.

Student Login

Login or join now!

Money Back Guarantee

Your purchase includes 100% 7-day money back guarantee.


If you are, for any reason, not entirely happy with your purchase, we will cheerfully issue you a full refund.